NIVELES DE DAÑO ECONOMICO DE Antigastra catalaunalis (Duponchel) EN AJONJOLI - RODRÍGUEZ-C., GILDARDO; ALVAREZ-R., J. ALONSO; MESA-F., ELOÍNA; GÓMEZ-G., ARIEL; SÁNCHEZ-G., GUILLERMO (Revista Colombiana de Entomología, 1987)
The sesame leafroller Antigastra catalaunalis (Duponchel) (Lepidoptera: Pyralidae) is the pest of major economic importance and its chemical control occupies the highest percentage of pest control in this crop. For this reason, the main goal of this study was to find out the level) of economic damage in three stages of the crop in order to reduce the amount of insecticide used. The research was carried out during 1982 at Nataima Regional Research Center of the Colombian Agricultural Institute (ICA), located in El Espinal, Tolima, at 431 m.s.s.1, average temperature of 27,5°C, an average rainfall of 1374,5 mm and 70% rélative humidity. An economic analysis was made by the Kilodny-Hirsch method, which allowed the establishment of the following economic damage levels: first semester (March to July) at 25 DAG, 34 larvae per 100 plants; at 40 DAG, 118 larvae per 100 plants and at 55 DAG, 98 larvae per 100 plants. Second semester (September-January) at 25 DAG, 17 larvae per 100 plants; at 40 DAG, 26 larvae per 100 plants, and at 55 DAG, 37 larvae per 100 plants. In both semesters, the results showed that plants support larger infestations at 40 DAG. On the other hand, the economical losses in the second term are half than that in the first, being this very much related to the yield obtained in both semesters.